Stature and Life-Time Labor Market Outcomes: Accounting for Unobserved Differences - Petri Böckerman; Jari Vainiomäki (Institute for the Study of Labor (IZA), 2013)
We use twin data matched to register-based individual information on earnings and employment to examine the effect of height on life-time labor market outcomes. The use of twin data allows us to remove otherwise unobserved ability and other differences. The twin pair difference estimates from instrumental variables estimation for genetically identical twins reveal a significant height-wage premium for women but not for men. This result implies that cognitive ability explains the effect of height on life-time earnings for men. Additional findings using capital income as the outcome variable suggest that discrimination against short persons may play a role for women.
Keywords: I10; J23; J31; 330; height; weight; BMI; height premium; earnings; employment